PERSEPSI KEPUASAN PASIEN RAWAT JALAN TERHADAP PELAYANAN PETUGAS DI BAGIAN PENDAFTARAN PADA PUSKESMAS SEMATANG BORANG PALEMBANG - Tutik Pebrianti; Sri Porwani (Universitas Indo Global Mandiri)
This research was conducted to find out the Perception of outpatient satisfaction to service officersin registration sectionat Puskesmas Sematang Borang Palembang.Data collecting was conducting by using questionnaire instruments in form of questions. The result of this research showed that: satisfaction of outpatient to service of lowest registration officer that is a statementof charge equal to 66,67%. The perception is most dominant from the outpatient satisfaction to service officers in registration section that is a statement of service officers in registration section with a courtesy of 81,67%. Keywords: Perseption, Outpatient Satisfaction, Service.